Irregularidades em parcerias com o terceiro setor: análise das decisões do TCE/GO utilizando inteligência artificial - Goes, André da Silva (2023)
This dissertation analyzes how the limitations and dysfunctionalities of the publicization model, in which the Public Administration transfers public equipment and delegates the provision of services to Third Sector entities, were addressed in the audits of the Court of Auditors of the State of Goiás. As a reference present in the literature review combined with exploratory research that used machine learning and artificial intelligence techniques, we sought to automatically identify and classify, through a predictive model, the main pathologies and irregularities identified by the Court of Accounts of Goiás in the relationships agreed between the civil society organizations and the public sector. The survey results point to the occurrence of irregularities in 84.05% of the total processes inspected by the external control body, indicating that the model of contracting in Goiás did not overcome the limitations and dysfunctionalities of contracting observed in the literature. The existence of gaps in the Legal Framework of the Third Sector was also demonstrated, providing an opportunity for the presentation of a recommendation to improve legislation with a focus on governance, through the suggestion of norms tending to promote ethical conduct, alternative forms of financing in the Third Sector Sector and that stimulate the expansion of the control activity focused on objectives, goals and results of the inspected partnerships.